Application of Spiky Nickel Nanoparticles to Hydrogen Evolution Reaction. (6th October 2020) - Abbas, Syed Asad; Ma, Ahyeon; Seo, Dongho; Lim, Yun Ji; Jung, Kwang‐Deog; Nam, Ki Min
Abstract : The development of an efficient water splitting catalyst is a requirement for sustainable hydrogen production. Ni catalysts with different shapes were prepared using a solvothermal method for hydrogen evolution reaction (HER). The growth of the Ni particles was manipulated by controlling the reaction temperature and surfactant during the solvothermal reaction. The HER activity of the herein obtained Ni catalysts, namely semi‐spherical, dendritic, and spiky nanoparticles were evaluated in alkaline conditions. Spiky Ni nanoparticles exhibited superior HER catalytic activity compared to that of spherical and dendritic Ni nanoparticles. The effect of morphology and electrochemical active sites has been fully investigated. Abstract : Spiky Ni nanoparticles exhibited superior HER catalytic activity compared to that of spherical and dendritic Ni nanoparticles.